Games and gaming in medieval literature - Patterson, Serina 1985- (The New Middle Ages, 2015)
The first-of-its-kind, Games and Gaming in Medieval Literature explores the depth and breadth of games in medieval literature and culture. Chapters span from the twelfth to the sixteenth centuries, and cover England, France, Denmark, Poland, and Spain, re-examining medieval games in diverse social settings such as the church, court, and household. Games and Gaming in Medieval Literature constitutes the first collection that explores the depth and breadth of games in medieval literature and culture. With geographical and methodological diversity of interdisciplinary scholarship, this volume presents fresh critical discussions of medieval games as vehicles for cultural signification, and challenges scholars to reconsider how games were understood by medieval writers, compilers, scribes, players, audiences, and communities. Chapters span from the twelfth to the sixteenth centuries, and cover Europe from England, France, Denmark, Poland, and Spain. This volume not only brings to the forefront a re-examination of medieval games in diverse social settings - the Church, the court, the school, and the gentry household - but also their multifaceted relation to literary discourses as systems of meaning, interactive experiences, and modes of representation.